Faktor-Faktor Yang Mempengaruhi Wanita Usia Subur Dalam Melakukan Deteksi Dini Kanker Serviks Metode Inspeksi Visual Asam Asetat (IVA) Di Wilayah Kerja Puskesmas Muara Emburung Kecamatan Rambang Niru Kabupaten Muara Enim Tahun 2023 - Sherin, Anggun Mutiara; aisyah, siti; Anggraini, arie (NHM PRESS, 2024)
The background of this research is that there are 613 (17.44%) mothers who carry out IVA examinations in the working area of the Muara Embird Health Center in 2022 and there are 2 mothers who experience IVA (+). This study aims to determine the relationship between the level of knowledge, access to information and cadre support simultaneously with the behavior of examining Acetic Acid Visual Inspection (IVA) in Women of Reproductive Age (WUS) in the Working Area of the Muara Embird Health Center, Rambang Niru District, Muara Enim Regency in 2023. The research design The method used is a quantitative descriptive study with a cross-sectional research design. Data collection techniques using questionnaires. The data obtained were analyzed using the chi square test. The research subjects were women of childbearing age (WUS) with a total population of 613 people and a sample of 30 respondents, the sampling technique was total sampling. The results obtained after using the chi square test found that the significance value was <0.05, which means that there is a relationship between the level of knowledge, access to information and support from cadres simultaneously with the behavior of Visual Inspection of Acetic Acid (IVA) examinations in Women of Reproductive Age (WUS) in the Region The work of the Muara Embird Health Center, Rambang Niru District, Muara Enim Regency in 2023